HUBUNGAN KEPATUHAN PENCEGAHAN KOMPLIKASI DENGAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Dewi, Siti Utami; Hapsari, Faricha Indra; Andani, Nur; Ramli, Ramli; Kartadarma, Supriyatni (Ensiklopedia of Journal, 2024)
Abstract: One of the leading causes of death that has continued to increase in recent years is cardiovascular disease, one of which is hypertension. Jembatan Kecil Health Center was recorded as the health center with the highest number of hypertension cases in 2023, with 7,007 people diagnosed with hypertension at the health center. The purpose of the study was to determine the relationship between compliance with prevention of complications with blood pressure in patients with hypertension. This type of research is quantitative using a cross sectional design. The research was conducted in the work area of Jembatan Kecil Health Center in 2023. The study population was all hypertensive patients who visited Posbindu in the work area of Jembatan Kecil Health Center, totaling 179 patients. The sample amounted to 60 respondents. Sample collection technique using purposive sampling. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between compliance with prevention of complications (p value: 0.00) to blood pressure. It is recommended for people with hypertension to routinely make efforts to screen blood pressure regularlyKeywords: Hypertension, Complications, Hypertension Prevention